Therapeutic Potential and Pharmaceutical Applications of Cucurbita - Malviya, Rishabha; Sharma, Akanksha (Current Nutrition & Food Science, 2021)
Aim: The present review aims to discuss the therapeutic potential and pharmaceutical applications of the Cucurbita plant. Methods: Various search engines such as ScienceDirect, Scopus, Google Scholar, Google Patents, etc. were used for the literature survey. Discussion: During the literature survey, it was observed that different parts of the Cucurbita species have significant therapeutic effects against disease conditions. They have antimicrobial, antifungal, antiviral, antiulcer, antidiabetic, anticancer, anti-inflammatory, etc., activities. Studies also showed that various pharmaceutical formulations have been prepared for the delivery of therapeutic active ingredients of cucurbits. A list of patents based on pharmaceutical formulations and therapeutic activity has also been included in the manuscript. Conclusion: It can be concluded from the findings that Cucurbita has significant therapeutic potential, clinical effects and can be used to treat various diseases.
Keywords: Herbal therapeutics